PP.37 The Antenatal Detection of Serious Cardiac Anomalies – Evaluating a Disparate Group Against a Target. (26th April 2013) - Berry, LE; Budd, JLS; Draper, ES
Abstract : Background: In 2010, the NHS Fetal Anomaly Screening Program (FASP) issued national targets for the antenatal detection rates (ADR) of "serious cardiac anomaly" at the 18 +0 –20 +6 week Fetal Anomaly Scan. There is no standardised definition for reporting for this heterogeneous group of anomalies. Here we evaluate the EUROCAT "serious cardiac group" against the FASP target of 50% antenatal detection, using data for 2010–2011 from the East Midlands and South Yorkshire Congenital Anomaly Register (EMSYCAR). Methods: Births between 01/01/2010 and 31/12/2011 reported to EMSYCAR as affected by one or more of the relevant cardiac ICD-10 codes were included in this analysis; cases associated with chromosomal anomalies were excluded. Birth prevalence and detection rates with 95% confidence intervals were calculated for each anomaly and compared to the FASP target. Results: The regional birth prevalence rate for the serious cardiac group was calculated; this varied between anomaly sub-groups from 0.59 to 4.42 per 10, 000 births. The ADR failed to reach the FASP target: (44.85%, 39.14%–50.66% ) though it was not significantly lower. Overall, 7 sub-groups reached the FASP target; 2 groups achieving statistical significance. Conclusion: The EUROCAT serious cardiac group of anomalies show wide ranging birth prevalence and ADR between the sub-groups, highlighting problems with standardised reporting. Given problems defining the group and the requirement for producing annual FASP target data at hospital level using small case numbers, there is major statistical uncertainty, leading to problems interpreting results. Standardisation of definitions and reporting will enhance the value of FASP targets for units.